How Does Acquisition Experience Affect Managerial Career Outcomes?. (5th June 2021) - Greene, Daniel; Smith, Jared
Abstract: We use hand-collected data from acquisition press releases to investigate how acquisition experience affects the career outcomes of non-CEO senior managers. To address the non-random nature of gaining experience, we separately use manager and firm-year fixed effects, as well as an instrumental variable analysis. Acquisition experience is positively related to compensation, the likelihood of a future board seat, and the likelihood of promotion to chief executive officer. Further tests suggest that the effects of experience decay over time, have diminishing returns, and do not depend on deal quality. Finally, we search Securities and Exchange Commission filings to document novel information on managerial roles in mergers and acquisitions.